Teachers’ Job Satisfaction: A Study in Secondary Schools of Bangladesh - Monira Jahan, Md. Meraz Ahmed, (JCTE, 2023)
This study was conducted to assess teachers’ job satisfaction in secondary schools of Bangladesh. Secondary school teachers i.e. 314 were selected randomly from purposively selected 6 teacher training centers (TTC) located in 4 different divisions in Bangladesh. This was a survey study within the nature of positivist and constructivist approaches as mix research method was used to generate data of the study. Data on teachers’ job satisfaction were collected by using questionnaire and focus group discussion. Brayfield-Rothe job satisfaction scale and Kanungo’s job involvement scale were adapted to measure teachers’ job satisfaction and job involvement respectively. The findings of the study indicated that most of the teachers were generally satisfied ranging from moderately satisfied to satisfied. Gender, school location, school type, attitude to benefits and job involvement were identified as robust predictors for teachers’ job satisfaction.